C‐Ski activates cancer‐associated fibroblasts to regulate breast cancer cell invasion. Issue 6 (27th August 2013) - Wang, Liyang; Hou, Yixuan; Sun, Yan; Zhao, Liuyang; Tang, Xi; Hu, Ping; Yang, Jiajia; Zeng, Zongyue; Yang, Guanglun; Cui, Xiaojiang; Liu, Manran
Abstract : Aberrant expression of c‐Ski oncoprotein in some tumor cells has been shown to be associated with cancer development. However, the role of c‐Ski in cancer‐associated fibroblasts (CAFs) of tumor microenvironment has not been characterized. In the current study, we found that c‐Ski is highly expressed in CAFs derived from breast carcinoma microenvironment and this CAF‐associated c‐Ski expression is associated with invasion and metastasis of human breast tumors. We showed that c‐Ski overexpression in immortalized breast normal fibroblasts (NFs) induces conversion to breast CAFs by repressing p53 and thereby upregulating SDF‐1 in NFs. SDF‐1 treatment or p53 knockdown in NFs had similar effects on the activation of NFs as c‐Ski overexpression. The c‐Ski‐activated CAFs show increased proliferation, migration, invasion and contraction compared with NFs. Furthermore, c‐Ski‐activated CAFs facilitated the migration and invasion of MDA‐MB‐231 breast cancer cells. Our data suggest that c‐Ski is an important regulator in the activation of CAFs and may serve as a potential therapeutic target to block breast cancer progression. Highlights: We demonstrate that c‐Ski can promote trans‐differentiation of NFs to CAFs. c‐Ski‐activated CAFs can accelerate the invasion of breast tumor cells. c‐Ski‐induced activation of CAFs may be associated with p53 and SDF‐1. c‐Ski represses p53 in fibroblasts is closely related to the activation of CAFs.